2001
DOI: 10.1038/35078527
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1 is a transcriptional target for E2F and p53

Abstract: Loss of function of the retinoblastoma protein, pRB, leads to lack of differentiation, hyperproliferation and apoptosis. Inactivation of pRB results in deregulated E2F activity, which in turn induces entry to S-phase and apoptosis. Induction of apoptosis by either the loss of pRB or the deregulation of E2F activity occurs via both p53-dependent and p53-independent mechanisms. The mechanism by which E2F induces apoptosis is still unclear. Here we show that E2F1 directly regulates the expression of Apaf-1, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
410
2
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(437 citation statements)
references
References 37 publications
19
410
2
5
Order By: Relevance
“…6,18,19 In our experiments using transient transfections, p53-deficient cells, as well as p53 siRNA, we could demonstrate that IKIP expression is dependent on p53 (Figure 7b, c and e). However, no regulation by E2F-1 could be observed (not shown).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…6,18,19 In our experiments using transient transfections, p53-deficient cells, as well as p53 siRNA, we could demonstrate that IKIP expression is dependent on p53 (Figure 7b, c and e). However, no regulation by E2F-1 could be observed (not shown).…”
Section: Discussionmentioning
confidence: 63%
“…p53 and also E2F have been shown to induce the expression of APAF1 at the transcriptional level. 5,6 Besides mitochondria, the endoplasmic reticulum (ER) has recently gained much attention for its role in apoptosis. 7,8 First, the ER can generate death signals of its own as the last consequence of the unfolded protein response.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Apaf-1 levels in post-mitotic cells such as cardiomyocytes and sympathetic neurons are markedly reduced (as compared to mitotic cells) [108,109,116], resulting in a significant decrease in apoptosome activity. The reduced activity of E2F1 [30], which is a transcriptional regulator of Apaf-1 [93] in terminally differentiated cardiomyocytes, is likely to contribute to the marked reduction of Apaf-1 in these cells. Given the reduced apoptosome activity (resulting from low levels of Apaf-1), endogenous XIAP has a greater inhibitory impact on apoptosis in post-mitotic cells.…”
Section: Apoptosismentioning
confidence: 99%
“…Apaf-1 and caspase 7) directly, or by suppressing antiapoptotic signals such as the activation of NF-kB Perhaps more simple to understand are a number of reports that have recently implicated E2F-1 as being a regulator of factors intrinsic to the apoptotic process, for example, apoptosis protein-activating factor (Apaf-1). 71,72 When induced, Apaf-1 assembles with cytochrome c, a mitochondrial signal released on receipt of apoptotic signals, and activates caspase 9 leading to the activation of downstream effector caspases eventually leading to apoptosis (Figure 3). 73 Although the death receptor and the Apaf pathways can be thought of as distinct, there is accumulating evidence that crosstalk occurs between all the different pathways, so the complex pattern of signal interaction must first be determined before the effects of individual signals can be seen.…”
Section: A Role In Cancermentioning
confidence: 99%